Effect of core muscles strengthening workouts in improving the static balance of judo players - Aboelwafa, H. S. (Sports Science and Health, 2022)
Core muscles have multiple benefits for athletes and non-athletes, such as their importance in improving motor performance and preventing injuries. Judo players perform various movements during training or matches, such as bending, rotation, and flexion, which depend heavily on the muscles around the torso as well as the balance requirements during throwing to reach the optimal position of the throw. This study aimed to verify the effectiveness of intense training during the preparation period to strengthen the core muscles on the static balance of the judo players. In total, 24 judo players participated in the study to form two groups: an experimental group (12 players), who were trained via intense core muscle workouts (8 exercises) according to specific instructions (three times per week / 6 weeks), and a control group (12 players), who were trained on various muscle groups (three times per week / 6 weeks). The Flamingo test (European Fitness Test-Euro Fit) was applied to measure the static balance of the players (pretest-posttest). The results showed an improvement in the static balance for both groups, the comparison between the two groups showed the experimental group indicated statistically significant changes (p < 0.05) than the control group in terms of static balance because of core muscle strengthening workouts. The results obtained confirm the effectiveness of core muscle strengthening workouts in improving the static balance of judo players. Therefore, coaches can use these workouts during the preparation period and can manage training loads according to the characteristics of the players by regularly measuring the static balance through field or laboratory, results of this tests can be help in planning training programs.